A Model‐Based Method for Design Option Evaluation of Off‐the‐Shelf Naval Platforms. Issue 1 (July 2017) - Morris, Brett A.; Cook, Stephen C.
Abstract: Off‐the‐Shelf (OTS) strategies have become prevalent in the acquisition of naval platforms because the strategy is perceived as a means of reducing the acquisition cost and schedule risk. This paper covers a method to conduct an evaluation of shortlisted OTS naval platform design options that utilises Model‐Based Systems Engineering (MBSE). MBSE is used as a means of developing and managing the traceability of evaluation criteria, managing the evaluation itself and facilitating reuse of the design patterns present both in naval platforms and acquisition processes. The paper concludes with a description of a pilot test of the method for an Offshore Patrol Vessel, which found it to be useful to manage the evaluation criteria traceability, maintain design data and identify weak spots in OTS design options.